DAMPAK PEMBANGUNAN INFRASTRUKTUR DESA PISA KECAMATAN TOMBATU KABUPATEN MINAHASA TENGGARA - POLUAN, KARTIKA KARINA; PANGKEY, MASJE SILLIJA; TAMPI, GUSTAAF BUDDY (JURNAL ADMINISTRASI PUBLIK, 2019)
Development in general is a process of change that is continuously carried out to get better. This study aims to find out how the impact of Infrastructure Development in Pisa Village, District of Tombatu, Southeast Minahasa Regency. The method used in this study is a qualitative descriptive method with an inductive approach. Qualitative descriptive approach is a method that describes problems or cases that are presented based on existing facts based on specific facts then examined to solve the problem and draw conclusions in general. Researchers use three indicators, namely, development is change, development is growth, and development is a series of businesses that are consciously done. Based on the results of the research, it was stated that the development realized in the village of Pisa in general was not optimal, this was demonstrated through the results that appeared that did not cause change. The government seems to be less consistent and government coordination towards the community is not optimal. This it can be concluded that the impact of Infrastructure Development in Pisa Village, Tombatu District, Sountheast Minahasa district does not cause changes and growth in developing the current development.Keywords : Impact, Development, Infrastructure, Village